WHO Polio Eradication Program: Problems and Solutions - S. M. Kharit; V. S. Pokrovsky; A. A. Ruleva; I. V. Fridman (Педиатрическая фармакология)
In 2013 WHO re-evaluated its main goals of the polio eradication program. A modernization program was accepted with regard to the National vaccination calendars worldwide which includes a step-by-step refusal from the living polio vaccine (OPV) and a total transition to the inactivated polio vaccine (IPV) starting in 2019. Because of the total eradication of the polio type 2 virus, as an intermediate step the 3-valence OPV was substituted with the 2-valence OPV, which does not contain the type 2 polio virus, in April 2016. The aim of the article is to present the history of polio prevention and to state the reasons for the adoption of 3rd edition of the Global Polio Eradication Initiative. The new approaches were defined for eradication of wild polio virus type 1 and vaccine related strains. A new strategy for global switch to inactivated polio vaccine by 2019 was suggested.